Latissimus dorsi musculocutaneous flap grafting to the infected recipient site in a patient with irradiated locally advanced breast cancer and multiple lung metastases - Yuki Ishii; Hitomi Matsuki; Nozomi Uozumi; Shoji Oura (Surgical Case Reports, 2023)
Abstract Background Musculocutaneous (MC) flaps are more resistant to infection than implants, but no clinical results have been reported so far about the grafting of MC flap to the overtly infected sites. Case presentation A 66-year-old woman had received radiotherapy, a total dose of 50 Gy, to her large mucinous breast cancer to control bleeding from the tumor and was referred to our hospital for further treatment. On her first visit to our hospital, her left breast showed radiation-induced total necrosis with Pseudomonas aeruginosa infection. Removal of the necrotic breast tissue resulted in direct exposure of the left ribs and intercostal muscles with intractable chest pain requiring analgesics. The presence of concomitant life-threatening multiple lung metastases made us change the treatment from letrozole and palbociclib to bevacizumab and paclitaxel, leading to marked regression of the lung metastases. To alleviate her chest pain and get local wound healing, we treated the patient with latissimus dorsi (LD)-MC flap grafting to the exposed chest wall after four months of taxane-containing chemotherapy. The patient has got marked pain relief immediately after the operation. Skin island of the grafted LD-MC flap showed no problems for 4 days just after the operation but gradually turned out to be edematous to ill-colored in the distal part of the skin island. Post-operative clinical outcome suggested that Pseudomonas aeruginosa infection might have had some adverse effect, e.g., microemboli, on MC flap blood flow. Partial necrosis of the LD-MC flap made the patient receive conservative wound management for a very long period of 11 months, finally leading to complete wound healing. After palliative surgery, the patient has been receiving fulvestrant and palbociclib for 14 months and doing well with good control of multiple lung metastases. Conclusions Breast surgical oncologists should note that partial flap necrosis can occur when a LD-MC flap is grafted to the infected recipient site and consider the anti-coagulant therapy just after the operation to avoid the adverse effects of the infection.